The Effect of Parasocial Relationship on Online Impulsive Buying Tendency: Exploring the Role of Financial Literacy and Self-Control - Ivana Sheruly; Andi Supandi Suaid Koentary (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Impulsive buying behavior has increased alongside the growth of digital transactions and technological advancements that simplify purchasing. Psychological studies have scientifically demonstrated that e-commerce website design and enjoyable online shopping experiences can trigger positive emotions that drive impulsive buying behavior, especially in women where self-esteem and body image have been proven to be contributing factors. The urgency to examine this issue has been amplified by the COVID-19 pandemic, which has been found to stimulate impulsive buying. With self-control and financial literacy as moderating factors, researchers are focusing on the phenomenon of impulsive buying among women in their early adulthood, as this age group is considered the most vulnerable to impulsive buying behavior. Researchers aim to investigate how self-control and financial literacy might mitigate the influence of parasocial relationships on impulse buying tendencies, with the ultimate goal of preventing individuals in early adulthood from getting trapped in the cycle of impulsive buying and its long-term ripple effects. Participants in this study are 195 women aged 18 to 25 who have a favorite celebrity figure and had purchased beauty products in the previous two months. According to the findings of simple regression analysis, parasocial relationships affect impulsive purchasing tendencies (F(1.191) = 12.100, p < .05, = .059, = .054). It was also discovered that self-control has a moderating role on the influence of parasocial relationships toward impulse buying tendencies (R =.4172, F(1.191) = 13.4189, p < .05), but financial literacy has no moderating role.